2019
DOI: 10.3390/nu11092258
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face and Digital Multidomain Lifestyle Interventions to Enhance Cognitive Reserve and Reduce Risk of Alzheimer’s Disease and Related Dementias: A Review of Completed and Prospective Studies

Abstract: Background: Currently, there is no pharmaceutical intervention to treat or delay pathological cognitive decline or Alzheimer’s disease and related dementias (ADRD). Multidomain lifestyle interventions are increasingly being studied as a non-pharmacological solution to enhance cognitive reserve, maintain cognition, and reduce the risk of or delay ADRD. Review of completed and prospective face-to-face (FTF) and digital multidomain interventions provides an opportunity to compare studies and informs future interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 95 publications
3
49
0
1
Order By: Relevance
“…Our results seem to be consistent with previous research which has shown that the adherence to overall healthier lifestyles are associated with better cognitive function in adulthood ( Lövdén et al, 2013 ; Klimova et al, 2017 ; Kivipelto et al, 2018 ; Bott et al, 2019 ; Mintzer et al, 2019 ). The mechanisms that underlie the relationship between lifestyle factors and cognition are not yet fully understood.…”
Section: Discussionsupporting
confidence: 93%
“…Our results seem to be consistent with previous research which has shown that the adherence to overall healthier lifestyles are associated with better cognitive function in adulthood ( Lövdén et al, 2013 ; Klimova et al, 2017 ; Kivipelto et al, 2018 ; Bott et al, 2019 ; Mintzer et al, 2019 ). The mechanisms that underlie the relationship between lifestyle factors and cognition are not yet fully understood.…”
Section: Discussionsupporting
confidence: 93%
“…167 In the same field, other trials targeted disease onset reduction through support in chronic disease management, smoking cessation, and health coaching. 168…”
Section: Past Evidencesmentioning
confidence: 99%
“…Multi-domain intervention studies are now being tested around the world. A recent review of completed and prospective multi-domain lifestyle programs aimed at enhancing cognitive reserve and reducing risk of ADRD reported 17 studies, 13 of which are face-to-face and 4 delivered digitally [3]. One of the main barriers to multi-domain intervention studies is adherence to the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Primary prevention of Alzheimer's disease and related dementias (ADRD) is increasingly studied as a risk reduction strategy in the absence of any currently available disease-modifying treatments [1,2]. Several interventions studied to-date have had mixed results, and a frequent barrier to these programs has been adherence [3]. One way to potentially improve adherence to risk reduction interventions is to engage patients in the design of the trial, especially when designing a personalized, multi-domain intervention.…”
Section: Introductionmentioning
confidence: 99%